Single-Cell Landscape of Lungs Reveals Key Role of Neutrophil-Mediated Immunopathology during Lethal SARS-CoV-2 Infection - Zheng, Xiao-Shuang; Wang, Qi; Min, Juan; Shen, Xu-Rui; Li, Qian; Zhao, Qiu-Chen; Wang, Xi; Jiang, Ren-Di; Geng, Rong; Chen, Ying; Zhu, Yan; Li, Bei; et al. (Journal of virology, 2022)
We demonstrated the single-cell landscape in lung and spleen upon SARS-CoV-2 infection in an acute severe disease mouse model that replicated human symptoms, including severe lung pathology and lymphopenia. Our comprehensive study revealed the key role of neutrophil-mediated lung immunopathology in SARS-CoV-2-induced severe pneumonia, which not only helped our understanding of COVID-19 but also warranted the concept of neutrophil targeting therapeutics in COVID-19 treatment. Due to the limitation of human studies with respect to individual difference or the accessibility of fresh tissue samples, how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection results in pathological complications in lung, the main site of infection, is still incompletely understood. Therefore, physiologically relevant animal models under realistic SARS-CoV-2 infection conditions would be helpful to our understanding of dysregulated inflammation response in lung in the context of targeted therapeutics. Here, we characterized the single-cell landscape in lung and spleen upon SARS-CoV-2 infection in an acute severe disease mouse model that replicates human symptoms, including severe lung pathology and lymphopenia. We showed a reduction of lymphocyte populations and an increase of neutrophils in lung and then demonstrated the key role of neutrophil-mediated lung immunopathology in both mice and humans. Under severe conditions, neutrophils recruited by a chemokine-driven positive feedback produced elevated “fatal signature” proinflammatory genes and pathways related to neutrophil activation or releasing of granular content. In addition, we identified a new Cd177 high cluster that is undergoing respiratory burst and Stfa high cluster cells that may dampen antigen presentation upon infection. We also revealed the devastating effect of overactivated neutrophil by showing the highly enriched neutrophil extracellular traps in lung and a dampened B-cell function in either lung or spleen that may be attributed to arginine consumption by neutrophil. The current study helped our understanding of SARS-CoV-2-induced pneumonia and warranted the concept of neutrophil-targeting therapeutics in COVID-19 treatment. IMPORTANCE We demonstrated the single-cell landscape in lung and spleen upon SARS-CoV-2 infection in an acute severe disease mouse model that replicated human symptoms, including severe lung pathology and lymphopenia. Our comprehensive study revealed the key role of neutrophil-mediated lung immunopathology in SARS-CoV-2-induced severe pneumonia, which not only helped our understanding of COVID-19 but also warranted the concept of neutrophil targeting therapeutics in COVID-19 treatment.